Activating dislocation mediated plasticity in boron carbide through Al-doping. (December 2022) - Yang, Qirong; Marvel, Christopher J.; Shen, Yidi; He, Mo-Rigen; Du, Jun; Hwang, Chawon; Gronske, Eric D.; Xie, Kelvin Y.; Mercurio, Steven R.; An, Qi; Harmer, Martin P.; Hemker, Kevin J.; et al.
Abstract: Dislocation slip, deformation twinning, phase transformations, and fast fracture are energy dissipation mechanisms that accommodate mechanical loading in materials. The energetically unfavorable formation of dislocation attributes to the ease of cracking and the low damage tolerance observed in superhard ceramics, notably boron carbide. This work demonstrates that room temperature dislocation slip can be enabled in boron carbide by altering its chemistry through Al doping. The activation of dislocation slip is mechanistically explained by quantum mechanics simulations and electron microscopy, which indicate that strain energy is released through basal icosahedral slip facilitated by icosahedral rotation and chain bond breaking and reconfiguring. The new insight gained from this work suggests that atomic doping could be an effective strategy to tune deformation mechanisms in boron carbide, which provides a significant potential for limiting amorphization and catastrophic failure, and opens a new strategy to enhance damage tolerance in brittle ceramics. Graphical abstract: Image, graphical abstract